1985
DOI: 10.1063/1.96286
|View full text |Cite
|
Sign up to set email alerts
|

Preferential nucleation along SiO2 steps in amorphous Si

Abstract: Annealing characteristics for amorphous Si film deposited on an SiO2 layer were investigated with the hope that this would throw further light on aspects of solid phase epitaxy. Preferential nucleation, which initiated from the bottom region of deposited Si film, was found along SiO2 steps. The activation energy for the growth speed of the nuclei was evaluated to be 1.7 eV. As this value is significantly smaller than 2.0 eV, the bond breaking energy of Si, stress originating mainly from the thermal expansion d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Although the mechanism of stress effects of a-Si:H film crystallization is not clearly understood, it is suggested that induced biaxial stress facilitates the crystallization process [16,17]. Kimura et al reported that silicon nitride (SiN x ) dielectric caps can impose a tensile stress on the underlying silicon layer during a post deposition anneal; they suggested that thermal stress is induced by the difference in the thermal coefficients of expansion (TCE) between a-Si (TCE = 2.3 × 10 − 6°C− 1 ), and silicon nitride (TCE = 3.3 × 10 − 6°C− 1 ) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism of stress effects of a-Si:H film crystallization is not clearly understood, it is suggested that induced biaxial stress facilitates the crystallization process [16,17]. Kimura et al reported that silicon nitride (SiN x ) dielectric caps can impose a tensile stress on the underlying silicon layer during a post deposition anneal; they suggested that thermal stress is induced by the difference in the thermal coefficients of expansion (TCE) between a-Si (TCE = 2.3 × 10 − 6°C− 1 ), and silicon nitride (TCE = 3.3 × 10 − 6°C− 1 ) [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that crystallization of a-Si starts at the interface between the a-Si film and the glass substrate, indicating the driving force of the uniaxial stress caused by the difference in the thermal expansion coefficient between a-Si and glass, leading to preferential nucleation along SiO 2 steps in a-Si. 14 On the other hand, there are some reports on the suppressing effect of the interfacial stress on the rate of crystallization and that nucleation starts at the surface of the a-Si rather than the interface, when a biaxial stress is induced from a fused silica substrate 15 or from an overlayer such as a Si 3 N 4 cap. 16 In the case of MIC, while the basic mechanism is still a subject of study, it has been claimed that compressive stress and lattice shrinkage caused by the introduced metal is the principal factor in Al-induced crystallization of a-Ge.…”
Section: Introductionmentioning
confidence: 98%
“…Techniques to promote nucleation in solid-phase crystallization (SPC) of amorphous silicon (a-Si) include Si ion implantation [3], the use of steps at the substrate surfaces [4][5][6], and metal induced lateral crystallization [7][8][9]. Of these previously reported techniques, only Si ion implantation can form a single-crystal grain at any desired position.…”
Section: Introductionmentioning
confidence: 99%